Living arrangements, health lifestyles, and health outcomes among Chinese oldest-old - Wang, Jie; Zhang, Lanxi; Wang, Shen; Zhang, Li (Frontiers in Public Health, 2023)
Prior literature has documented a strong correlation between living arrangements and older adults' health outcomes. However, few studies have explained why this association exists. This study took health lifestyle theory approach and brought health lifestyles into the link between living arrangements and Chinese oldest old health outcomes. It examined 1) whether health lifestyle behaviors among oldest old varied by household contexts, 2) whether the health disparities among Chinese oldest old in different household contexts could be partially explained by their health lifestyles. Using the most recent 2018 data released by the Chinese Longitudinal Healthy Longevity Survey (CLHLS), latent class analysis was applied to identify predominant health lifestyles among Chinese oldest old aged 85 to 105. Three distinct classes representing health lifestyles of Chinese oldest old emerged; health lifestyle patterns were found to vary by elders' living arrangements. The respondent's health lifestyles in diverse residential structures served as a mediator which can partially explain the health disparities among the oldest old.Results highlighted the importance of family, lifestyles and cultural contexts to health of the oldest old.